ANALISIS PENGARUH PERTUMBUHAN EKONOMI, INFLASI DAN UPAH MINIMUM REGIONAL TERHADAP PENGANGGURAN DI DKI JAKARTA TAHUN 1997-2012 - , FALDI ALIF; , Samsubar Saleh, Prof. Dr., M.Soc.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze the impact of economic growth, inflation rates, and minimum wage on the rate of unemployment in DKI Jakarta during 1997-2012. This study uses a multiple linear regression analysis with 3 independent variable with 16 consequents time. The result of the study shows that economic growth and minimum wage variable has a negative and significant effects toward the unemployment in DKI Jakarta, while the inflation rate variable has a positive and significant effect on the unemployment in DKI Jakarta during 1997-2012.